2019
DOI: 10.1097/gox.0000000000002491
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis Influence on the Perfusion in Perforator Flaps in Early Postoperative Period: A Series of 18 Cases

Abstract: Introduction: In practice worldwide, there are experiences affecting different body functions via central control mechanisms with the help of psychotherapy methods. In plastic and reconstructive surgery, there is the experience of applying hypnosis, with the main goal of eliminating pain. The aim of this research is to study the impact of hypnosis on the perfusion level in perforator flaps in the early postoperative period, which could enhance flap survival. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For instance, Badiul et al found that hypnosis can significantly increase perfusion in perforator flaps. 53 Furthermore, Hoxhallari et al found that hand surgery patients exhibited less anxiety when they used virtual reality during wide awake local anaesthesia with no tourniquet. 54 Finally, virtual reality/augmented reality systems can be implemented for renal interventions, such as renal cell carcinoma treatment, and the training of oral and maxillofacial surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Badiul et al found that hypnosis can significantly increase perfusion in perforator flaps. 53 Furthermore, Hoxhallari et al found that hand surgery patients exhibited less anxiety when they used virtual reality during wide awake local anaesthesia with no tourniquet. 54 Finally, virtual reality/augmented reality systems can be implemented for renal interventions, such as renal cell carcinoma treatment, and the training of oral and maxillofacial surgeons.…”
Section: Discussionmentioning
confidence: 99%